SPECTRUM COMPILATION FOR FATIGUE TEST AND LIFE PREDICTION OF VEHICLE CONTROL ARM - HUA FeiFei; ZHENG SongLin; FENG JinZhi; YU JiaWei (Jixie qiangdu)
Only the fatigue damage of low amplitude loads was considered in the traditional spectrum compilation method.The strengthening effect of the low amplitude loads of components was neglected. In the present study,the program loading spectrum for a vehicle control arm durability test was developed. Then,the fatigue life of this control arm was predicted based on the traditional fatigue damage theory and the low amplitude loads strengthening theory respectively,the difference between these two theories on fatigue life prediction was compared and analysized. The bench test results shows that the fatigue life can be predicted more accurately by considering the strengthening effect of low amplitude loads,and it is significant to predicate the failure mode of durability tests and to estimate durability of mileage of auto components more accurately.